The Role of Artificial Intelligence in Improving the Performance of Green Marketing for SMEs - Fills Prayoga; Diah Probowulan; Haris Hermawan (International Journal of Education Management and Religion, 2026)
Artificial Intelligence (AI) has emerged as a transformative force in the evolution of digital marketing, particularly for small and medium-sized enterprises (SMEs) striving to integrate sustainability into their competitive strategies. This study analyses the contribution of AI technologies to enhancing the performance and efficiency of green marketing initiatives within SMEs operating in the digital economy. The research employs a systematic literature review method by synthesizing peer-reviewed publications from 2020 to 2025. The findings demonstrate that AI-driven applications—such as machine learning, predictive analytics, and automated engagement systems—enable SMEs to personalize eco-oriented messages, identify environmentally conscious consumer segments, and measure campaign outcomes with higher precision. Moreover, the adoption of AI supports improvements in resource efficiency, targeting accuracy, and assessment of both social and environmental impacts. The evidence further indicates that SMEs utilizing AI in sustainable marketing experience increased customer loyalty, stronger brand reputation, and greater long-term competitiveness. Despite these benefits, several challenges remain, including limited digital readiness, high implementation costs, and insufficient technological capabilities among SMEs. Overall, integrating AI into green marketing practices presents a promising pathway for SMEs to achieve sustainable growth while meeting the expectations of environmentally aware consumers in the digital era. Future research is encouraged to develop affordable and user-friendly AI tools tailored to the marketing needs of small businesses.